Characterization of Kawista Fruit Peel (Limonia accidisima L.) from Pasinan Village, Pasuruan - Prastyaningtias, Sisca Desi; Dian Sari, Agung Suci; Salsinha, Yustina Carolina Febrianti (Jurnal Agroekoteknologi, 2023)
Kawista Fruits, which originates from India, were found in Pasinan village, Lekok, Pasuruan, East Java. People generally use this plant as med-icine, one of which is to cure diarrhea. That fuits has been consumed leaves quite a lot of fruit peel. One effort to utilize kawista fruit peel waste is to process into a useful material. Based on the research results, Kawista fruit peel extract at a concentration of 100% was effective in inhibiting the growth of Salmonella sp bacterial colonies. The characteristics of the raw materials for using kawista fruit peel as an antibacterial are very important to maintain the quality of the ingredients and to ensure the uniformity of their properties. Despite of that, information on the secondary metabolite content of kawista peel is also very important to know what compounds are useful as antibacterials. Based on the results of research using phytochemical analysis, the results obtained were that the secondary metabolite compounds contained in kawista fruit skin were flavonoid, terpenoid, alkaloid, saponin and tannin. Meanwhile, the results of the simplicia characterization showed that the drying shrinkage level was 10.516%, the air content was 4.778%, the ash total content was 10.918%, the air soluble essence content was 23.673%, and the ethanol soluble essence content was 12.756%. Based on standard parameter conditions, the drying shrinkage content, water content, air soluble essence content, and ethanol soluble essence content have met the standard parameters. Meanwhile, the total ash content does not meet the standard parameter requirements.